2014
DOI: 10.1002/clen.201400256
|View full text |Cite
|
Sign up to set email alerts
|

Sonolytic Decolorization of Textile Wastewater Containing a Mixture of Reactive, Acid and Disperse Dyes

Abstract: The effect of chemical additives in combination with ultrasonication (US) was evaluated for the decolorization of simulated synthetic textile wastewaters containing Reactive Black 5 (RB5), Congo Red (CR), and Disperse Blue 3 (DB3). Maximum decolorization of 93% was achieved for the wastewater containing RB5 (50 mg L À1 ) at 8 h sonication time and US power density of 1 W mL À1. Persulfate (PS) assisted US was appeared to be better over the sodium sulfate (SS)-assisted US, giving 87.51% decolorization efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although some level of control is needed to define and characterize a dye degradation system, a more realistic approach toward system development should be adopted, incorporating research on real effluents or mixtures of dyes. Although it is mainly the mixtures of dyes that are encountered in the actual effluents from textile industry, there are very limited reports examining such mixtures of dyes and even fewer that include an anthraquinone dye within the dye mixture. ,, The absence of extended research on dye mixtures (only one review paper on dye mixture decolorization was found) highlights the need to investigate the ability of existing technologies to treat a more realistic form of effluent, that being dye mixtures, or solutions containing other auxiliaries used in the textile industry. Focusing on decolorization of anthraquinone dyes by immobilized oxidoreductases, the lack of information on the performance of such systems on real (or realistic) effluents was also noted.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…Although some level of control is needed to define and characterize a dye degradation system, a more realistic approach toward system development should be adopted, incorporating research on real effluents or mixtures of dyes. Although it is mainly the mixtures of dyes that are encountered in the actual effluents from textile industry, there are very limited reports examining such mixtures of dyes and even fewer that include an anthraquinone dye within the dye mixture. ,, The absence of extended research on dye mixtures (only one review paper on dye mixture decolorization was found) highlights the need to investigate the ability of existing technologies to treat a more realistic form of effluent, that being dye mixtures, or solutions containing other auxiliaries used in the textile industry. Focusing on decolorization of anthraquinone dyes by immobilized oxidoreductases, the lack of information on the performance of such systems on real (or realistic) effluents was also noted.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…The RB21 solution was prepared by dissolving a certain amount of RB21 in deionised water. Synthetic textile effluent was prepared by dissolving equal amount of RB21, RB19, RV5, and RR198 in tap water along with the other chemical additives, as described by Verma et al 23…”
Section: Preparation Of Aqueous Rb21 and Synthetic Textile Effluentmentioning
confidence: 99%